Prospects and challenges for supply chain trade under the Africa Continental Free Trade Area - Jaime De Melo; Anna Twum (Journal of African Trade, 2021)
African countries are negotiating the African Continental Free Trade Area with the aim to spearhead global value chain (GVC) trade among African countries as a driver for robust economic growth. This paper evaluates the participation of Sub-Saharan African Regional Economic Communities (RECs) in GVC-related trade over the period 1990-2015 using measures of backward, forward, regional, and non-regional GVC participation. We find that participation of African RECs in GVC trade (regional and non-regional) has increased but still lags behind comparator groups. Overall, African RECs have participated mostly in non-regional value chains, and along forward rather than backward activities. This is in contrast to comparator groups where supply chain trade has veered toward regional value chains (RVCs). For African RECs, only between 0.5% and 3% of total gross exports are related to RVCs compared to the RVC participation rates for the Association of Southeast Asian Nations (ASEAN) and the Southern Common Market (MERCOSUR): 17.2% and 4.6%, respectively. Controlling for per capita income, we find, using a sample of 149 countries over the period 1995-2015, that overall GVC participation is negatively associated with tariffs on imports and exports of intermediates as well as on trade costs. Backward GVC participation is also positively associated with the number of mobile phone subscribers, a proxy for digital connectivity. These correlations are supportive of policies that would lower trade barriers across the board.
Keywords: F14; F15; L23; O11; O55; 330; Africa; trade; global value chains; supply chain trade